Per un’analisi non significante della soggettività: la funzione del punto-segno ne l’Anti-Edipo - Tolfo, Davide (Philosophy Kitchen - Rivista di filosofia contemporanea, 2018)
The aim of this article is to investigate the correlation between semiotic and the question of subjectivity in Deleuze and Guattari’s Anti-Oedipus. For doing so, the first part explores how Deleuze and Guattari move away from a negative interpretation of desire, and rethink in a productive way the movement and the investments of desire. This premise is fundamental to understand the nature and the function of a concept that, at first sight, seems to be irrelevant, the notion of pointsign. This concept is important for two reasons: indeed, it has a central role in both untangling the relationship that - inside the Lacan’s approach to psychoanalysis - connects desire to signifier and in creating a different relation between sign and desire. Finally, I will show how these semiotic considerations can be used as tools to search and investigate the new process of subjectification inside our contemporaneity.